(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-1-194-205 The paper deals with the possibilities of using information and communication technologies in the educational process, electronic and mobile learning technologies in particular. The paper defines and presents the content of the initial concepts of the research. Special attention is paid to a mobile application as a modern and effective learning tool. Mobile apps have a number of specialized capabilities which can be used in the educational process. The paper reveals positive and negative aspects of their use. It carries out a comparative analysis of existing mobile applications used in teaching the Russian language and written business communication and presents the prospects for their use. The authors come to the conclusion about the insufficient number and quality of mobile applications that could be used in developing business writing skills. The material of the paper can be helpful for teachers of universities, technical and secondary schools for the purpose of self-education and increasing the efficiency of the educational process. Key words: information and communication technologies, distance learning, e-learning, mobile learning, mobile application, written business communication, business letter